Marked reduction of Tamm-Horsfall protein synthesis in hyperprostaglandin E-syndrome - Schröter, Jens; Timmermans, Gundi; Seyberth, Hansjörg W.; Greven, Jürgen; Bachmann, Sebastian (Kidney international, 1993)
Marked reduction of Tamm-Horsfall protein synthesis in hyperprostaglandin E-syndrome. Hyperprostaglandin E-syndrome (HPS), a recently described variant of Bartter's syndrome (BS), resembles BS in a number of symptoms but is distinct from BS in others. Similar to BS, HPS is characterized by congenital hypokalemic alkalosis, hypertrophy of the juxtaglomerular apparatus, hyperreninemia, secondary hyperaldosteronism, normal blood pressure and renal diabetes insipidus. Other than BS, HPS is constantly associated with chronic hypercalciuria and nephrocalcinosis as well as both renal and systemic PGE2 overproduction. Correction of most of the symptoms in HPS is achieved by permanent inhibition of prostaglandin synthesis with indomethacin. Among the causes leading to HPS, a selective damage of the distal tubule in HPS has been suggested. Therefore, synthesis of Tamm-Horsfall protein (THP), a glycoprotein exclusively produced in the thick ascending limb of the loop of Henle, was measured by ELISA in the urine of seven infant HPS patients (aged 3 to 8 years). Patients were investigated both under constant indomethacin treatment and after a one week period without indomethacin. Nine healthy children (aged 5 months to 10 years) served as controls. In controls mean daily THP excretion was 54.2 ± 13.9 (median 46.0) mg/24 hr/1.73 m2 whereas in HPS, THP levels were strongly diminished. During withdrawal of indomethacin treatment, mean THP level was 12.7 ± 10.1 (median 7.2) mg/24 hr/1.73 m2 and 10.3 ± 10.1 (median 3.5) mg/24 hr/1.73 m2 under indomethacin treatment, respectively. THP excretion values both without indomethacin and under indomethacin treatment were significantly different from controls (P ≤ 0.005); however, there was no significant difference between the THP levels during or after cessation of indomethacin treatment. Creatinine clearance in HPS patients was 75.1 ± 15.9 (median 76.2) ml/min/1.73 m2 without indomethacin and 81.9 ± 15.1 (median 83.0) ml/min/1.73 m2 under indomethacin treatment. Control values were not obtained. Comparative measurements of THP excretion in six classical BS-patients (aged 3 months to 17 years) revealed normal THP values in two individuals and intermediate levels in the others: the mean level of six BS patients was 30.8 ± 13.5 (median 25.0) mg/24 hr/1.73 m2 and was thus significantly higher than in HPS both with and without indomethacin treatment (P ≤ 0.05). Immunohistochemistry in renal biopsies of three of the HPS patients showed a strong reduction of cortical tubular THP immunoreactivity in two cases and a less pronounced reduction in the third. In situ hybridization using a THP-riboprobe in these three biopsies revealed significantly reduced or absent THP-mRNA levels. The severely decreased THP-production supports previous assumptions that one of the major causes underlying HPS is a selective congenital defect of the distal tubule. Differences in THP excretion between HPS and BS support a concept that defines HPS and BS as separate entities with a number of similarities.